The Tithonian-Lower Valanginian stratigraphy and ammonite fauna of the Vaca Muerta Formation in Pampa Tril, Neuquén Basin, Argentina - Parent, Horacio (2015)
Fil: Fil: Parent, Horacio. Laboratorio de Paleontología, IFG-FCEIA, Universidad Nacional de Rosario, Argentina.